Road Transportational Accident Analysis of Urban to Town Connecting Sectors - B M, Divya; G K, Ravi Kumar; S V, Shashikala (Journal of Neonatal Surgery, 2025)
- Road safety is worlds safety; we used to leave our half of the life in road transport only. Without transportation we can’t do anything. As per the analysis of world record of death rate 6-11 % of death is by road accident. Either riding, or walking or even standing in footpath, we can’t miss accident. Our errors contribute to the world safety is of 68% help from human life to environment and world economic state balancing, keeping this in mind. This paper done with few analysis of urban connection and accident road ways. Road safety is not a small factor to neglect .It needs a thousand of alarm to avoid or not to see death as soon.